Analisis Penerapan Value Creation Selling dalam Strategi Pemasaran Perusahaan Jasa Logistik: Studi Kasus di PT XYZ - Darjat Sudrajat (Bina Nusantara University, 2012)
A company is a market-oriented when the culture of value creation superior customer systematically and comprehensively implemented on company concerned. Value can be defined as the ratio of benefit to cost, where customers expect a rate of return equal or exceed the costs they incurred to obtain the products they bought. From the case studies conducted on PT XYZ, then, in getting the project tender delivery of goods geophysical equipment for the Brunei Loon project, it has been implemented value selling creation, which includes three main components, ie customer portraits, the proposed value, and benefits to customers or total value of ownership. Overall, the efficiency given value is about 20% compared to its closest competitor, the safety shipping and on time, as well as the positive benefits of the profit margin, cash flow, return on investment, brand equity, market share and customers.